ENZYME AND ANTIOXIDANT PROFILE OF FOLLICULAR FLUID IN SHEEP - G. Suganya; V. Leela; N. Jayanthi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The follicular fluid consists of locally produced substances that act as regulatory factors in follicular development and steroidogenesis. Among the various constituents, alkaline phosphatase, lactate dehydrogenase and antioxidants in the follicular fluid provide information about the metabolic activities and degenerative changes that take place in the cells during follicular growth. Hence, this study was conducted to evaluate the enzyme and antioxidant concentrations of follicular fluid in relation to follicular size. About two hundred and fifty pairs of ovaries of Madras Red sheep in apparently good health were randomly collected after slaughter from Corporation Abattoir, Chennai. Follicular fluid was aspirated from small (less than 2 mm), medium (2-4 mm) and large (greater than 4 mm) ovarian follicles and centrifuged in a cooling centrifuge at 4oC at 3000 rpm for 15 minutes. The supernatant fluid from the three categories of follicles was collected and analyzed for alkaline phosphatase, lactate dehydrogenase, antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxide as per the standard protocol. The data were analyzed statistically by ANOVA. It was observed that the alkaline phosphatase and lactate dehydrogenase activity significantly decreased (P < 0.05) as the follicle size increased. The activity of superoxide dismutase and catalase significantly decreased (P < 0.05) with an increase in follicle size whereas, glutathione peroxidase activity significantly increased (P < 0.05) with increased follicle size.